Efficacy, Safety and Immunogenicity of Sun’s Ranibizumab Biosimilar in Neovascular Age-Related Macular Degeneration: A Phase 3, Double-Blind Comparative Study - Asim K. Ghosh; Usha S. Nikumbh; Chaitanya K. Shukla; Rohit S. Laul; Abhishek Dixit; Santosh K. Mahapatra; Sameera Nayak; Urmil M. Shah; Sandeep Parwal; Narendran Venkatapathy; Natasha Radhakrishnan; Anup Kelgaonkar; et al. (Ophthalmology and Therapy, 2024)
Abstract Introduction The study aimed to evaluate comparability in terms of efficacy, safety and immunogenicity of Sun’s ranibizumab biosimilar with reference ranibizumab in patients with neovascular age-related macular degeneration (nAMD). Methods This prospective, randomised, double-blind, two-group, parallel-arm, multicentre, phase 3 comparative study included patients with nAMD ≥ 50 years, randomised (in a 2:1 ratio) in a double-blind manner to receive 0.5 mg (0.05 mL) intravitreal injection of either Sun’s ranibizumab or reference ranibizumab in the study eye every 4 weeks until week 16 (total of four doses). Results Primary endpoint results demonstrated equivalence in the proportion of patients who lost fewer than 15 letters from baseline best-corrected visual acuity (BCVA) to the end of week 16 (99% of patients in Sun’s ranibizumab and 100% in reference ranibizumab; p > 0.9999), with the proportional difference (90% confidence interval) at −1% (−2.51, +0.61) lying within a pre-specified equivalence margin. Visual acuity improved by 15 or more letters in 43% of Sun’s ranibizumab group and 37% of the reference ranibizumab group (p = 0.4267). The mean increase in BCVA was 15.7 letters in Sun’s ranibizumab group and 14.6 letters in the reference ranibizumab group (p < 0.001 within both groups and p = 0.5275 between groups). The mean change in central macular thickness was comparable between groups (p = 0.7946). Anti-ranibizumab antibodies were found in one patient of the reference ranibizumab group, while neutralising antibodies were not found in any patients. Both products were well tolerated. Conclusion Sun’s ranibizumab biosimilar is found to be therapeutically equivalent to reference ranibizumab in patients with nAMD. There were no additional safety or immunogenicity concerns. Trial Registration CTRI/2020/09/027629, registered on 07 September 2020.